Modelagem preditiva do uso e cobertura da terra do Estado de Mato Grosso Sul, Brasil - BRUNO HENRIQUE MACHADO DA SILVA (2024)
The State of Mato Grosso do Sul has been standing out nationally due to its development in the agriculture and forestry sector, becoming an economic powerhouse. However, land use and land cover changes can cause a series of environmental problems, which impact the reduction of carbon stocks and sequestration, mainly deforestation and forest fires, requiring proper land management. The objective of the work is to carry out predictive modeling of land use and land cover for the years 2030 and 2050 for business-as-usual (BAU) and forest development scenario (FD) scenarios. The proposed methodology is based on the multitemporal analysis of land use and land cover and applying the CA-Markov/Random Forest model to perform predictive simulations of future scenarios. The results point to the predominance of pasture between 1985 and 2020 (53%) with significant vegetation suppression (21% of perch). Following the state pattern, the pasture showed a significant growth pattern in the mesoregion of the Pantanais Sul Matogrossenses (36%). In the current context, the Central North and Southwest mesoregions have advanced and developed export agriculture (growth of 9% and 26% of the occupied area). In contrast, in the Eastern mesoregion, silviculture is projected to have the highest growth (8.25%). For 2030 and 2050, the dynamics of the BAU sought to understand the productive logic, demonstrating the expansion of agriculture throughout the state (3% and 6%), followed by local growth such as silviculture (1% and 2.2%) and the decrease in pastures (-2% and -6%), except for the western region. It is understood that the FD sought to employ zones to encourage the preservation, conservation, and development of biodiversity, based on Brazilian legislation, regenerating 5% in 2030 and 8% in 2050 of natural vegetation compared to BAU, being able to achieve satisfactory results to the environment through its application. It is concluded that the state of Mato Grosso do Sul has undergone several transformations of the landscape, accompanied by environmental damage (deforestation and fires) however, followed by full economic development. Thus, the future scenarios emerge as a tool to understand dynamics of land use and land cover, being the expansion, maintenance, and regression of use; in this way, the scenarios have different objectives but can be worked together aiming at development economic and environmental, thus serving as an instrument for public management for planning and ordering land use and land cover.